Penerapan Kegiatan Teknis pada Kesehatan Masyarakat Veteriner tentang NKV terhadap Kesehatan Hewan di Dinas Ketahanan Pangan dan Pertanian Kota Blitar: Artikel Pengembangan - Moeis, Edya Moelia; Winarto, Winarto (Universitas Islam Balitar, 2022)
The research aims to implement and describe a technical activity related to the veterinary community regarding NKV for animal health. The importance of providing NKV needs to be fostered in an effort to facilitate trade considering that the smooth trading of animal food products requires an acknowledgment or legitimacy in the form of giving NKV in the form of a certificate explaining the achievement of technical standards/requirements based on objectivity, trustworthiness and transparency of assessment by the authorized agency/institution. Through NKV certification, besides being able to facilitate supervision and monitoring of food safety of animal origin, as well as tracking issues related to food safety, NKV owned by a business unit can also be the identity of the company. The results of the research and service show that there is a graph of a significant increase between before and after technical activities on animal health at the Blitar city food security office.